Alkene selenenylation: A comprehensive analysis of relative reactivities, stereochemistry and asymmetric induction, and their comparisons with sulfenylation - Soloshonok, Vadim A.; Nelson, Donna J. (Beilstein Journal of Organic Chemistry, 2011)
A broad perspective of various factors influencing alkene selenenylation has been developed by concurrent detailed analysis of key experimental and theoretical data, such as asymmetric induction, stereochemistry, relative reactivities, and comparison with that of alkene sulfenylation. Alkyl group branching α to the double bond was shown to have the greatest effect on alkene reactivity and the stereochemical outcome of corresponding addition reactions. This is in sharp contrast with other additions to alkenes, which depend more on the degree of substitution on C=C or upon substituent electronic effects. Electronic and steric effects influencing asymmetric induction, stereochemistry, regiochemistry, and relative reactivities in the addition of PhSeOTf to alkenes are compared and contrasted with those of PhSCl.
Keywords: alkene selenenylation; asymmetric synthesis; calculations; electronic effects; regioselectivity; relative reactivities; steric effects